Identification of novel Trichoderma hamatum genes expressed during mycoparasitism - Margaret Carpenter; Alison Stewart; Hayley Ridgway (浙江大学学报. 农业与生命科学版, 2004)
Trichoderma species are currently used as biocontrol agents for crop diseases caused by a number of fungal plant pathogens. However, their biocontrol performance in the field can be unreliable and it is likely that more consistent performance could be achieved through knowledge and manipulation of the genes involved. For example, induction of the genes could be optimised for variable environmental and physiological conditions, superior strains could be selected more effectively and novel strains could be created. One method by which Trichoderma species accomplish biocontrol is mycoparasitism. Several genes involved in the mycoparasitic interaction have previously been characterised, however these consist predominantly of those that encode enzymes that degrade fungal cell walls.In the current study subtractive hybridisation was used to target genes expressed when Trichoderma hamatum and the plant pathogen Sclerotinia sclerotiorum were cultured together, subtracting genes expressed when each are grown individually. This experimental design has the potential to yield T. hamatum genes involved in mycoparasitism of S. sclerotiorum, and S. sclerotiorum genes up-regulated in host defence. The cDNA fragments yielded by the subtraction were characterised with respect to expression, sequence and species of origin. A number of novel T. hamatum genes which were up-regulated during mycoparasitism were identified.